Detection of carbapenemase production in gram negative bacilli in medical and surgical intensive care unit patients in a tertiary care hospital - Kadel S; Bilolikar AK; Eswaran SP; Krishnaveni M; Fatima R; Sahu S (Journal of Medical and Scientific Research, 2023)
Background: Carbapenem-resistant Enterobacterales (CRE) are an urgent global public health problem. CRE infections are associated with high mortality and have limited available effective treatment. Carbapenemase enzymes are encoded by genes on mobile genetic elements, such as plasmids, which are highly transmissible between organisms and increase the potential spread of resistance. The study aim was to detect carbapenemase production in Gram negative bacilli by phenotypic (CarbaNP and mCIM only or in conjunction with eCIM) and genotypic (Xpert Carba-R) methods.